Organization of Phonemic Space Represented by The Units of Spectra and Spectral Changes - Shirai, Katsuhiko; Mano, Kazunor i (Canadian Acoustics, 2022)
This paper describes a method of organization of Phonemic space for phoneme recognition. Phonemic space Is obtained by clustering speech spectra and spectral changes. Power change, LPC cepstral coefficients and the differences of LPC cepstral coefficients are used to represent the characteristics of the spectral contour and spectral change. The efficiency Is shown by an experiment of phoneme recognition.